Biochar addition stabilized soil carbon sequestration by reducing temperature sensitivity of mineralization and altering the microbial community in a greenhouse vegetable field. (1st July 2022) - Zhang, Xi; Zhang, Qianqian; Zhan, Liping; Xu, Xintong; Bi, Ruiyu; Xiong, Zhengqin
Abstract: Biochar is widely used for soil carbon sequestration and fertility improvement. However, the effects of biochar interacted with nitrogen (N) on the mineralization of soil organic carbon (SOC) and microbial community have not been thoroughly understood, particularly no reports have been published on the long term effects of biochar in vegetable field. Here, we examined soil properties, SOC mineralization and microbial community affecting by biochar (0, 20 and 40 t ha −1 ; C0, C1 and C2, respectively), N (0 or 240 t ha −1 ; N0 or N1, respectively) and their interaction in a greenhouse vegetable field. Results indicated that biochar addition increased soil pH, SOC, recalcitrant C pool, especially for the 40 t ha −1 treatment. Biochar addition generally decreased soil C-cycling enzyme activity while increasing N and P-cycling enzyme and oxidase activities. Biochar combined with N addition reduced SOC mineralization rate and metabolic quotient ( q CO2 ) by 10.2–22.0% and 6.85–30.4%, respectively, across 15–35 °C and the temperature sensitivity ( Q 10 ) by 0.96–4.70%, except for the N1C2 at 25–35 °C. Apparent changes in bacterial alpha diversity and community structures were observed among treatments. Besides, biochar mixed with N application significantly enhanced the relative abundance of Proteobacteria and decreased Acidobacteria, while did not result in significant differences in fungal diversity and community composition. Redundancy analysis indicated that the microbial community composition shifts induced by the interaction between N and biochar were attributed to the changes in soil chemical properties, such as pH and SOC. Overall, the combination of biochar and N fertilizer is recommended to improve SOC sequestration potential and regulate bacterial community diversity and composition in vegetable field for sustainable intensification. Graphical abstract: Image 1 Highlights: Biochar altered soil properties after long-term incorporation in a vegetable field. Biochar improved soil N and P-cycling enzyme activities and C sequestration. Biochar combined with N reduced mineralization rate and q CO2 across 15–35 °C. Biochar affected bacterial not fungal community composition in vegetable field.